2009
DOI: 10.1210/me.2008-0387
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Regulated Pathways Associated with Endometriosis

Abstract: Endometriosis is a prevalent gynecological disease characterized by growth of endometriotic tissue outside the uterine cavity. MicroRNAs (miRNAs) are naturally occurring posttranscriptional regulatory molecules that potentially play a role in endometriotic lesion development. We assessed miRNA expression by microarray analysis in paired ectopic and eutopic endometrial tissues and identified 14 up-regulated (miR-145, miR-143, miR-99a, miR-99b, miR-126, miR-100, miR-125b, miR-150, miR-125a, miR-223, miR-194, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
210
5
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(229 citation statements)
references
References 64 publications
10
210
5
4
Order By: Relevance
“…Despite extensive research, the pathogenesis of endometriosis remains unclear because it is complex. Recently, several studies have revealed that aberrant miRNA profiles are correlated with endometriosis (Ohlsson Teague et al, 2009;Braza-Boïls et al, 2014;Rekker et al, 2015). In particular, our own and previous studies indicated that members of the miR-200 family (miR-200a, miR-200b, and miR-200c) were downregulated in endometriosis-associated tissues (Ohlsson Teague et al, 2009;Braza-Boïls et al, 2014;Rekker et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…Despite extensive research, the pathogenesis of endometriosis remains unclear because it is complex. Recently, several studies have revealed that aberrant miRNA profiles are correlated with endometriosis (Ohlsson Teague et al, 2009;Braza-Boïls et al, 2014;Rekker et al, 2015). In particular, our own and previous studies indicated that members of the miR-200 family (miR-200a, miR-200b, and miR-200c) were downregulated in endometriosis-associated tissues (Ohlsson Teague et al, 2009;Braza-Boïls et al, 2014;Rekker et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…There is accumulating data that miRNAs contribute to the pathogenesis of endometriosis by regulating abnormal cell differentiation, invasion, and inflammation 23. It has been reported that the expression of several miRNAs differs between the eutopic and ectopic endometrial tissues of women with and without endometriosis 9, 24. The authors recently reported that the down‐regulation of miR‐542‐3p expression in eutopic endometrial stromal cells enabled morphological and biological differentiation of the endometrium 13.…”
Section: Discussionmentioning
confidence: 99%
“…Filtered gene lists provided as supplemental data must be provided as Excel spreadsheets and not PDFs. Specific examples of supplemental data accompanying gene expression profiling manuscripts can be found in Ohlsson Teague et al (2009); supplemental data available at: (http://mend.endojournals.org/cgi/content/full/ me.2008-0387/DC1).…”
Section: Genomicsmentioning
confidence: 99%